Human engineered heart tissue as a versatile tool in basic research and preclinical toxicology. - Sebastian Schaaf; Aya Shibamiya; Marco Mewe; Alexandra Eder; Andrea Stöhr; Marc N Hirt; Thomas Rau; Wolfram-Hubertus Zimmermann; Lenard Conradi; Thomas Eschenhagen; Arne Hansen (PLoS ONE, 2011)
Human embryonic stem cell (hESC) progenies hold great promise as surrogates for human primary cells, particularly if the latter are not available as in the case of cardiomyocytes. However, high content experimental platforms are lacking that allow the function of hESC-derived cardiomyocytes to be studied under relatively physiological and standardized conditions. Here we describe a simple and robust protocol for the generation of fibrin-based human engineered heart tissue (hEHT) in a 24-well format using an unselected population of differentiated human embryonic stem cells containing 30-40% α-actinin-positive cardiac myocytes. Human EHTs started to show coherent contractions 5-10 days after casting, reached regular (mean 0.5 Hz) and strong (mean 100 µN) contractions for up to 8 weeks. They displayed a dense network of longitudinally oriented, interconnected and cross-striated cardiomyocytes. Spontaneous hEHT contractions were analyzed by automated video-optical recording and showed chronotropic responses to calcium and the β-adrenergic agonist isoprenaline. The proarrhythmic compounds E-4031, quinidine, procainamide, cisapride, and sertindole exerted robust, concentration-dependent and reversible decreases in relaxation velocity and irregular beating at concentrations that recapitulate findings in hERG channel assays. In conclusion this study establishes hEHT as a simple in vitro model for heart research.